Dilema Hak Atas Pekerjaan dalam Kebijakan Pasar Tenaga Kerja Fleksibel - Syahwal Syahwal (Jurnal HAM, 2022)
The right to work demands the role of the State in its fulfillment but the development of a flexible labor market poses a dilemma for the state in fulfilling the right to work. This study was conducted by using a normative type of research that examines the right to work in a flexible labor market using a statutory approach. In Indonesia, the flexible labor market is embodied in the Job Creation Act, which describes the state's dilemmatic position in carrying out its duties for the right to work. Against this dilemmatic position, the state prioritizes job creation over the feasibility of the jobs created. Based on this research, the author outlines the importance of a holistic approach in viewing human rights in the legislation process. So that the availability of work and the feasibility of work are not placed separately. This is because indecent work places the degree of human beings, who are trying to be protected by human rights, in a vulnerable position.